Mechanism of Acid-Triggered Cargo Release from Lipid Bilayer-Coated Mesoporous Silica Particles - Dolstra, Cassidy C (Langmuir : the ACS journal of surfaces and colloids, 2019)
Lipid bilayer-coated mesoporous silica nanoparticles are unique core-shell nanomaterials currently being developed as drug delivery vehicles. To improve cargo loading and biocirculation, the pore structure and surface chemistry of the particle have been modified and well characterized. However, an understanding of cargo release mechanisms from cellular uptake pathways remains largely unexplored. Here, we present a study of the release mechanism of lipid bilayer-coated silica particles induced by endosomal-like pH change from 7.4 to 5.0. We found that this relatively small pH change produces rapid deformation of the supported lipid bilayer that ultimately results in holes in the membrane. Using a combination of dye release studies, wide-field and confocal fluorescence microscopies, and surface area modeling analysis, we determined that small blister-like structures are formed, which lead to lateral membrane displacement and hole formation. Possible mechanisms for the blister formation, which include curvature effects and interfacial interactions, are discussed